Pengaruh Citra Merek, Harga, Serta Promosi Terhadap Loyalitas Pelanggan Kartu Smartfren di Sugi Celuller Banjarmasin - Muhammad Fajar Aditya; Abdurrahim A; Apriya Santi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to examine the effects of Brand Image, Price, and Promotion on Customer Loyalty to Smartfren cards at Sugi Celluler Banjarmasin, both simultaneously, partially, and dominantly. The research design is quantitative and is conducted as a survey study. The results show that all the variables investigated—Brand Image, Price, and Promotion—have a significant effect on the independent variable when considered simultaneously. For the partial effect on Customer Loyalty to Smartfren cards at Sugi Celluler Banjarmasin, the Brand Image variable is the most influential. Furthermore, the variable that has the most dominant effect on Customer Loyalty to Smartfren cards at Sugi Celluler Banjarmasin is also the Brand Image variable. This is evidenced by the Coefficient table, where the Brand Image variable has the largest "Standardized Coefficient Beta" value of (0.526), whereas the Price and Promotion variables have values of (0.289) and (-0.002), respectively.